Joint random subcarrier selection and channel-based artificial signal design aided PLS - Naderi, Sanaz; da Costa, Daniel Benevides; Arslan, Hüseyin (IEEE - Institute of Electrical and Electronics Engineers, Inc., 2020)
A novel method for providing physical layer security (PLS) depending on the randomness of wireless channel is proposed. Specifically, a channel-based joint random subcarrier selection and artificial signal design are introduced to protect the communication in the presence of a strong passive eavesdropper. Our analysis assumes a window-based subcarrier selection method in which the strongest subcarriers in each window are selected. Chosen subcarriers are considered for secret sequence extraction. In addition the generated channel dependent secret sequence is used for both random subcarrier selection and artificial signal design. We evaluate the efficiency of the proposed method through some representative metrics, such as secret sequence disagreement rate (SSDR), throughput and bit error rate (BER), in both perfect and imperfect channel estimation cases. Simulation results are presented and insightful discussions are drawn.
Keywords: Channel Adaptive Secret Sequence; Channel Based Artificial Signal Design; Physical Layer Security; Random Subcarrier Selection; TDD; Window-Based Subcarrier Selection